Synthesis, anti-bacterial and anti-protozoal activities of amidinobenzimidazole derivatives and their interactions with DNA and RNA - Andrea Bistrović; Luka Krstulović; Ivana Stolić; Domagoj Drenjančević; Jasminka Talapko; Martin C. Taylor; John M. Kelly; Miroslav Bajić; Silvana Raić-Malić (Taylor & Francis Group, 2018)
Amidinobenzimidazole derivatives connected to 1-aryl-substituted 1,2,3-triazole through phenoxymethylene linkers 7a-7e, 8a-8e, and 9a-9e were designed and synthesised with the aim of evaluating their anti-bacterial and anti-trypanosomal activities and DNA/RNA binding affinity. Results from anti-bacterial evaluations of antibiotic-resistant pathogenic bacteria revealed that both o-chlorophenyl-1,2,3-triazole and N-isopropylamidine moieties in 8c led to strong inhibitory activity against resistant Gram-positive bacteria, particularly the MRSA strain. Furthermore, the non-substituted amidine and phenyl ring in 7a induced a marked anti-bacterial effect, with potency against ESBL-producing Gram-negative E. coli better than those of the antibiotics ceftazidime and ciprofloxacin. UV-Vis and CD spectroscopy, as well as thermal denaturation assays, indicated that compounds 7a and 8c showed also binding affinities towards ctDNA. Anti-trypanosomal evaluations showed that the p-methoxyphenyl-1,2,3-triazole moiety in 7b and 9b enhanced inhibitory activity against T. brucei, with 8b being more potent than nifurtimox, and having minimal toxicity towards mammalian cells.